Unsur Budaya dan Arsitektur Tradisional sebagai Potensi Daya Tarik Wisata di Desa Wisata Pengotan Kabupaten Bangli - Putrawan, Hendra; Putra, I G Agung Diasana (Sekolah Vokasi, Universitas Gadjah Mada, 2022)
Cultural and architectural elements are very important to be used as attraction in a Tourism Village. One example of a village that utilizes this potential as a tourist attraction is Pengotan Tourism Village. Pengotan Tourism Village was chosen in this study because of the existence of cultural and architectural elements that are still thick and need to be preserved. There are various traditions that characterize Pengotan Tourism Village that do not exist anywhere else. In terms of architecture, Pengotan Tourism Village still applies the concept of traditional architecture which is directly related to the natural resources that are owned around the village and the pattern of activities of its inhabitants is still influenced by their outlook on life. There are interesting things about the architecture of the Pengotan Tourism Village settlement, which on the one hand shows the diversity of its architecture and on the other hand it still shows consistency in the form and layout of the building. In this study, the things that want to be studied are what traditions are used as tourist attractions in Pengotan Tourism Village and how is the architecture of Pengotan Tourism Village settlements.